Fatigued surgeons: A thematic analysis of the causes, effects and opportunities for fatigue mitigation in surgery. (September 2021) - Whelehan, Dale F.; Brown, Daniel J.; Connelly, Tara M.; Ridgway, Paul F.
Abstract: Background: High-pressured situations, coupled with diminished resource allocations and over-worked staff have been characteristic of surgery for a long time before the COVID-19 pandemic. Understanding the cause and effects of fatigue in the profession are warranted to design evidence-based and effective interventions for fatigue mitigation. By identifying the individual stressors to individuals fatigue levels, tailored approaches to better optimise performance can be established. Methods: This was a single-site qualitative study design using an interpretive, iterative and then deductive thematic analysis approach. Participants were recruited between February 2020–May 2020. A convenience, followed by purposive sampling strategy was employed to inform theoretical gaps on surgical trainees and consultants. Findings: There are commonalities in the influencing factors between both fatigue and sleep deprivation. It was identified that often the combination of fatigue and sleep stressors blurs the line between identifying what is primarily influencing subjective fatigue. There was an appreciation that the perfect storm of personal and environmental stressors could impact patient safety. Participants identified several personal mitigators for technical and cognitive performance, but relied more heavily on team factors for decision-making and to mitigate affective issues. Conclusion: This study provides understanding of fatigue in surgery as a multifaceted phenomenon. Variation in causes and effects of fatigue are the norm. Maladaptive strategies to mitigate fatigue in surgery are commonly used. Fatigue as a problem is best tackled at an individual level, and supported by environmental and systemic changes to sustain behaviour changes.